The effect of silane-containing universal adhesives on the immediate and delayed bond strength of repaired composite restorations - Razieh Hoseinifar; Niloofar Shadman; Farnaz Mirrashidi; Sajad Gholami (Wolters Kluwer Medknow Publications, 2021)
Background: The repair of composite restorations is considered as a conservative treatment for avoiding the risk of pulp injury, the enlargement of cavity preparation, and excess removal of sound dental structure. The aim of this study was to evaluate the effect of silane-containing adhesives on immediate and delayed shear bond strength (SBS) of repaired composite restorations.Materials and Methods: In this in vitro study, 132 discs of Z350 composite were fabricated and divided into fresh (10 min water storage) and aged (6-month water storage + 2000 thermal cycling). All composite surfaces were roughened and etched, and each group was divided equally into six subgroups: 1 (Single Bond 2), 2 (Single Bond Universal), 3 (Clearfil Universal Bond), 4 (silane + Single Bond 2), 5 (silane + Single Bond Universal), and 6 (silane + Clearfil Universal Bond). The specimens were restored with the same composite, thermocycled, and tested for SBS in a universal testing machine. Data were analyzed using one- and two-way ANOVA, t-test, and post hoc Tukey's tests. P < 0.05 was set as the level of significant.Results: The highest and lowest SBS (in both fresh and aged groups) were related to Single Bond 2 with silane and Clearfil Universal Bond with silane, respectively. The delayed SBS of Single Bond 2 was significantly higher than universal adhesives (in both with and without silane application) (P < 0.05). Silane had no significant effect on the repair bond strength of Single Bond 2 and Single Bond Universal (P > 0.05), while silane application significantly decreased the delayed SBS of Clearfil Universal Bond.Conclusion: The SBS of Single Bond 2 was significantly better than two other universal adhesives. The SBS of Single Bond Universal was not affected by silane application, while silane had a negative effect on delayed SBS of Clearfil Universal Bond.